The effect of stress on reproduction and reproductive technologies in beef cattle—A review - Fernández-Novo, Aitor; Pérez-Garnelo, Sonia S.; Villagrá, Arantxa; Pérez-Villalobos, Natividad; Astiz, Susana (MDPI, 2021)
Researchers have contributed by increasing our understanding of the factors affecting reproduction in beef, mainly physical health and nutrition aspects, which have been main concerns during decades. Animal welfare is of outmost relevance in all animal production systems and it is strongly associated to stress. Stress responses involve endocrine, paracrine and neural systems and the consequences of this stress on the reproductive efficiency of specifically, beef cattle and bulls, need to be highlighted. We, therefore, describe the fundamentals of stress and its quantification, focusing in beef herds, reviewing the highly valuable pieces of research, already implemented in this field. We examine major factors (stressors) contributing to stress in beef cattle and their effects on the animals, their reproductive performance and the success of reproductive biotechnologies. We include terms such as acclimatization, acclimation or temperament, very relevant in beef systems. We examine specifically the management stress due to handling, social environment and hierarchy or weaning effects; nutritional stress; and thermal stress (not only heat stress) and also review the influence of these stressors on reproductive performance and effectiveness of reproductive biotechnologies in beef herds. A final message on the attention that should be devoted to these factors is highlighted.